Classroom Management: An Elixir to Pre-Schoolers Motivation and Affection toward Learning and School in Edo South Senatorial Districts - Florence Ikponmwen Iyamu (Sociometry Journal of Social Science, Art and Humanity, 2021)
Early education of children in Nigeria has been of great concern to parents, educators, and other stakeholders in education. This has led to a high investment in the educational sector, bus less progress is made at the pre-primary level. Many questions have arisen as to why this low progress has been made. Some attributed this low progress to the issue of classroom management, teacher motivation, and many more. This study, therefore, examined classroom management as a prerequisite to pre-schoolers motivation and affection toward learning and school in Edo South senatorial districts. The study was descriptive, and four research questions were raised to guide the study. The target population comprised classroom teachers in private and public pre-primary schools in the Edo South senatorial district of Edo State. The sample for this study was five hundred (500) teachers drawn from private and public pre-primary schools in the senatorial district. The research instrument used for this study was a questionnaire designed by the researchers. It was a four-Likert scale. It had two sections; Section A consists of the respondents' demographic data while Section B contains the questions that elicited responses from the respondents with response options like, Strongly Agree, Agree, Strongly Disagree, and Disagree. Three experts in the field determined the face and content validity of the instrument. Cronbach alpha method was used to ascertain the reliability of the instrument. It gave an alpha value of 0.89, indicating that the instrument was reliable. Data gathered through the questionnaire were analyzed using mean and standard deviation. A criterion mean of 2.50 was used to accept the items. In contrast, an interpretative norm of 7.50, the product of the criterion mean and the number of items in each cluster, was used to ascertain the extent of teachers' classroom management and motivation on children's affection for school. The findings proved that classroom management affects children's motivation and affection for learning and school. However, teacher motivation was not significant. Therefore, it was concluded that classroom management is a significant factor in facilitating pupil motivation and affection to learning and school. The study recommended that School teachers go for periodical in-service training on classroom management courses. Moreover, Education stakeholders should invest more in the learning environment and make it more attractive to learners by providing all necessary learning facilities.